You can simplify the given expression by taking out those factors who are perfect squares.
The simplified form of the given expression will be [tex]\dfrac{\sqrt{3}}{2}[/tex]
If possible, try to defactor what is inside the root.
For example, if 8 is under square root, then you can defactor 8 as made up of 2 times 2 times 2. Since 2 times 2 is perfect square, thus this can come out of the root.
Simply, some more such methods can be used to simplify these type of values.
[tex]\dfrac{3\sqrt{8}}{4\sqrt{6}} = \dfrac{3\sqrt{2 \times 2 \times 2}}{4\sqrt{6}}\\\\ \dfrac{3\sqrt{8}}{4\sqrt{6}} = \dfrac{3 \times 2\sqrt{2}}{4\sqrt{6}}\\ \\ \dfrac{3\sqrt{8}}{4\sqrt{6}} = \dfrac{6\sqrt{2}}{4\sqrt{6}} = \dfrac{\sqrt{6}\sqrt{2}}{4}\\\\ \dfrac{3\sqrt{8}}{4\sqrt{6}} = \dfrac{\sqrt{12}}{4} = \dfrac{\sqrt{4 \times 3}}{4} = \dfrac{\sqrt{3}}{2}[/tex]
Thus, after getting simplified, the expression becomes [tex]\dfrac{\sqrt{3}}{2}[/tex]
Learn more about quotient here:
https://brainly.com/question/16076853